COOLING GLOVE COMPARTMENT OF A VEHICLE BY THERMOELECTRIC COOLERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this study, effects of the four different thermoelectric cooler (TEC) placements on the boundaries of the glove compartment have been numerically investigated under the effect of natural convection with Boussinesq approximation. The best cooling capacity has been observed for the top boundary TEC application for the investigated glove compartment geometry. It has also been observed that heat transfer is stronger at the beginning of the process as a result of the stronger convection currents. The absorbed heat from the glove compartment increases with the increase of the electric current applied.